2016
DOI: 10.1371/journal.pmed.1002166
|View full text |Cite
|
Sign up to set email alerts
|

Promoting Partner Testing and Couples Testing through Secondary Distribution of HIV Self-Tests: A Randomized Clinical Trial

Abstract: BackgroundAchieving higher rates of partner HIV testing and couples testing among pregnant and postpartum women in sub-Saharan Africa is essential for the success of combination HIV prevention, including the prevention of mother-to-child transmission. We aimed to determine whether providing multiple HIV self-tests to pregnant and postpartum women for secondary distribution is more effective at promoting partner testing and couples testing than conventional strategies based on invitations to clinic-based testin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

22
279
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 243 publications
(318 citation statements)
references
References 23 publications
22
279
2
Order By: Relevance
“…If they refused to test for HIV, it is likely that their female partners would think that their refusal is related to their apparent HIV infection or promiscuity status. Nevertheless, our findings reaffirm previous findings from other studies that show that female-delivered HIVST is acceptable and can improve male partner and couples’ HIV testing [2,3,16]. …”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…If they refused to test for HIV, it is likely that their female partners would think that their refusal is related to their apparent HIV infection or promiscuity status. Nevertheless, our findings reaffirm previous findings from other studies that show that female-delivered HIVST is acceptable and can improve male partner and couples’ HIV testing [2,3,16]. …”
Section: Discussionsupporting
confidence: 91%
“…These findings suggest a need for alternative HIV-testing approaches that can help to improve HIV-testing rates among men, including female-delivered HIVST. However, while previous studies have reported impressive HIV-testing uptake rates among male partners and couples following female-delivered HIVST [2,3], only one study has explored the strategies that women used to deliver HIVST kits to their male partners [5]. Even then, this study did not document men’s reactions to receiving kits from their female partners.…”
Section: Introductionmentioning
confidence: 89%
See 2 more Smart Citations
“…Furthermore, self-test kits can be used in secondary distribution to test family members who are not home during home-or community-based testing initiatives. 8 Using index client testing through invitation not only of partners but also of children to the facility has also enhanced uptake of HIV testing using a family-centered approach. 9 Expanding index client testing to other members of the community (often within an integrated health screening approach) may further increase uptake of HIV testing services among family units.…”
Section: Family-centered Differentiated Hiv Testingmentioning
confidence: 99%